PEMUNGUTAN PAJAK PADA INVESTASI KRIPTO (TAX COLLECTION ON CRYPTO INVESTMENT) - Siti Ayu Rahayu (ITB AAS INDONESIA, 2023)
This study aims to analyze the implementation of crypto investment transactions that apply in Indonesia and the tax collection system for these crypto investments. This article uses normative legal research methods or doctrinal research. The sources of legal materials used are primary legal materials and secondary legal materials. The procedure for collecting legal materials in this article is by studying documents or library materials. Analysis of legal material sources is carried out descriptively by using a statutory approach and a conceptual approach. The results of the study concluded that in Indonesia, cryptocurrency is still not a legal means of payment. However, BAPPEBTI considers cryptocurrencies as valuable assets as investment assets. Crypto investment tax collection refers to the provisions contained in the Minister of Finance Regulation Number 68/PMK.03/2022 concerning Value Added Tax and Income Tax on Crypto Asset Trading Transactions.